Barriers to access to ear and hearing care services in low- and middle- income countries: A scoping review. Issue 12 (2nd December 2022) - Waterworth, Christopher J.; Marella, Manjula; O'Donovan, James; Bright, Tess; Dowell, Richard; Bhutta, Mahmood F.
ABSTRACT: People living in low- and middle- income countries (LMICs) meet significant challenges in accessing ear and hearing care (EHC) services. We conducted a scoping review to identify and summarise such barriers, to recognise gaps in the literature, and to identify potential solutions. Reviewers independently screened titles, abstracts and full-text articles and charted data. We undertook thematic analysis of supply and demand side dimensions of access, and summarised findings mapped against the Levesque framework. Of 3048 articles screened, 62 met inclusion criteria for review. Across the five access dimensions, supply-side constraints were more frequently described, the most common being a shortage of EHC workforce or appropriate facilities, despite high demand. We identified a thin geographical spread of literature on barriers to accessing EHC services in LMICs, reflecting low availability of such services. LMICs face a diverse range of demand and supply side challenges including workforce, equipment and resource shortages, and challenges for the majority of the population to pay for such services. There is a need for many LMICs to develop health policy and programmes in EHC, including integration into primary care, scaling up the EHC workforce through increased training and education, and improving EHC literacy through public health measures.